The sustainable development of Asian students’ project-based learning: Implementing a holistic and indigenous Whare Tapa Rima Model - Zhang, Xiudi; Tian, Xiaoming (Frontiers in Psychology, 2022)
This study employs a holistic and indigenous theoretical model called Whare Tapa Rima to examine the project-based learning experiences of Asian students in a private training establishment, the W institution, at the tertiary level in New Zealand. The analysis shows that Asian students face challenges in their PBL journey in physical, cultural, interconnected emotional and intellectual, social, and spiritual dimensions. Implications from the research analysis may be considered about how to provide better support and international services to Asian students involved in PBL programs worldwide by adopting the responsive, theory-informed framework of the Whare Tapa Rima Model.